Barriers to Utilization of Sexual Health Services among Young People in District Dang Nepal: A Qualitative Study - Gautam, Prayas; Soomro, Munawar Hussain; Sapkota, Suprich; Gautam, Koshish Raj; Kasaju, Aastha (Journal of Medicine, 2018)
Background: Sexual behavior of young people is becoming one of the important social and major publichealth concerns in recent years. Despite the large population of young people, their needs receive limited programmatic and policy attention. Youth-friendly sexual and reproductive health services are lacking despite the existence of national guidelines that call for youth-friendly services. The aim of this study was to determine the barriers to utilization of sexual health services among young people of Badi community of Nepal. Materials & Methods: This qualitative study included the young people, 15-24 years of age among the Badi community in district Dang Nepal. We conducted 22 in-depth interviews by using the interview guideline among the young people. Written and verbal informed consent was taken from each research participants before data collection. Results: Fourteen of the participants were males and eight were females. Participants were divided into two age groups: 15-19 and 20-24 and there were eight and fourteen participants from each group respectively. Rural participants were not satisfied with the services provided to them. We observed that discrimination, beliefs of society and feeling of shame towards family norms, lack of information about existing services, poor gender friendly services,lack of privacy and confidentiality and poor availability of the services pose the barriers to utilization of the sexual health services. Conclusions: Communities should be provided with educational programs on sexual health through community based organization and the establishment of youth friendly service centers with easy access to communities in urban as well as in rural areas would encourage young people to use sexual health services more frequently. J MEDICINE JUL 2018; 19 (2) : 79-83